2019
DOI: 10.1002/jcpy.1089
|View full text |Cite
|
Sign up to set email alerts
|

The Feeling of Not Knowing It All

Abstract: How do consumers assess their mastery of knowledge they have learned? We explore this question by investigating a common knowledge consumption situation: encountering opportunities for further learning. We argue and show that such opportunities can trigger a feeling-of-not-knowing-it-all (FONKIA), which lowers consumers' confidence in their mastery of the knowledge they already possess. Specifically, listing optional follow-up readings at the conclusion of a course lowered students' confidence in their mastery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Feeling like one has shallow knowledge of a particular topic is an aversive psychological state that people are motivated to reduce (e.g., the “feeling of not knowing it all” effect: Yang et al., 2019). Repeat consumption may uniquely promote feelings of newly learned mastery and expertise as a function of discovering new information about the stimulus at each repeated exposure, thereby sustaining enjoyment.…”
Section: The Psychological Process Of Repeat Consumptionmentioning
confidence: 99%
“…Feeling like one has shallow knowledge of a particular topic is an aversive psychological state that people are motivated to reduce (e.g., the “feeling of not knowing it all” effect: Yang et al., 2019). Repeat consumption may uniquely promote feelings of newly learned mastery and expertise as a function of discovering new information about the stimulus at each repeated exposure, thereby sustaining enjoyment.…”
Section: The Psychological Process Of Repeat Consumptionmentioning
confidence: 99%
“…Recent research suggests that positive affect can also increase sensitivity to omissions by increasing cognitive flexibility (Mantel et al, 2020). Debiasing techniques, such as a priori ratings of presented and omitted attributes (Kardes et al, 2006), a priori criteria consideration (Kardes et al, 2006), consider-the-unknown technique (Walters et al, 2016), the feeling of not knowing it all (Yang et al, 2019), and the distrust mindset (Gaffney et al, 2020), also improve judgment by increasing sensitivity to omissions. When omissions are detected, consumers attempt to fill gaps in knowledge by forming attribute-based, attitude-based, category-based, or schema-based inferences.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures that reduce epistemic certainty or overconfidence have been found to be effective in reducing omission neglect. Methods such as a priori ratings of presented and omitted attributes (Kardes et al, 2006), a priori criteria consideration (Kardes et al, 2006), consider-the-unknown technique (Walters et al, 2016), highlighting nonalignable differences in comparative judgment contexts (Sah & Read, 2020;Sanbonmatsu et al, 1997Sanbonmatsu et al, , 2003, the feeling of not knowing it all (Yang et al, 2019), and the distrust mindset (Gaffney et al, 2020) reduce overconfidence and decrease estimates of the strength of the available evidence. Epistemic uncertainty, or uncertainty stemming from a lack of knowledge, is distinct from aleatory uncertainty, or uncertainty stemming from a stochastic or probabilistic environment (Fox & Ülkümen, 2011).…”
Section: Omission Neglect In Learning and Memorymentioning
confidence: 99%
“…However, when prompted to detect missing information, consumers reduce their confidence in the available information and form more moderate and appropriate evaluations (Gunasti and Ross, 2009;Kardes et al, 2006;Sah and Read, 2020;Sanbonmatsu et al, 2003;Walters et al, 2017). Strategies such as encouraging individuals to elaborate on their criteria for judgment (Kardes et al, 2006), deliberately forming inferences about unmentioned product attributes (Gunasti and Ross, 2009;Sanbonmatsu et al, 1991), processing comparative information of non-alignable differences (Kardes and Sanbonmatsu, 1993;Sanbonmatsu et al, 2003), employing the consider-the-unknown technique (Walters et al, 2017), or stimulating the feeling of not knowing it all (Yang et al, 2019) have been shown to enhance the perception of missing attributes in product evaluation tasks. When missing information is made more salient, the confidence in the strength of available evidence is decreased, pushing consumers to adjust their evaluations and moderate their judgments (Kardes et al, 2006;Sanbonmatsu et al, 1991Sanbonmatsu et al, , 1997.…”
Section: Omission Neglectmentioning
confidence: 99%